THE EFFECT OF STEM PRACTICES ON PRE-SERVICE TEACHERS’ BELIEFS ON NATURE OF SCIENCE, THEIR ATTITUDES TOWARDS SCIENTIFIC RESEARCH AND CONSTRUCTIVIST APPROACH - Yıldırım, Bekir; Şahin, Emine; Tabaru, Gizem (My University, 2017)
öğretmen adaylarının bilimin doğası inançları, bilimsel araştırma ve yapılandırmacı yaklaşıma yönelik tutumları üzerine etkisi incelenmiştir. Araştırma, 2016-2017 eğitim-öğretim yılı güz dönemi boyunca bir üniversitenin eğitim fakültesi, STEM Eğitim laboratuvarında verilen Fen ve Teknoloji dersi kapsamında gerçekleştirilmiştir. Çalışmaya eğitim fakültesi fen bilgisi öğretmenliği anabilim dalında öğrenim gören 24 öğretmen adayı katılmıştır. Araştırma nicel bir çalışma olup, araştırma deneysel desenlerden tek gruplu ön test-son test modeline göre gerçekleştirilmiştir. Verilerin analizinde bağımlı ve bağımsız gruplar için t-testi, aritmetik ortalama, standart sapma kullanılmıştır. Araştırmada elde edilen bulgular ışığında, STEM uygulamalarının öğretmen adaylarının bilimin doğası inançları ve yapılandırmacı yaklaşım üzerine olumlu etkisi olduğu istatistiki olarak bulunmuştur. Ancak bilimsel araştırmaya yönelik tutumları üzerine anlamlı bir farkın olmadığı tespit edilmiştir. Kısacası, STEM uygulamalarının öğretmen adaylarının bilimin doğası inançları ile yapılandırmacı yaklaşım üzerine olumlu etkisinin olduğu söylenebilir. Bunun üzerine STEM eğitimi konusunda öğretmen adayı, öğretmen ve akademisyenlere yönelik önerilerde bulunulmuştur

In this study the effect of Science, Technology, Engineering, Mathematics (STEM) practices on pre-service science teachers’ beliefs on nature of science, their attitudes towards scientific research and constructivist approach has been examined. The research has been conducted during the fall semester of the 2016-2017 academic year within the scope of the Science and Technology course which have been given at the STEM Training Laboratory of faculty of education in a university. Twenty four pre-service teachers who have attended to department of science education of the faculty of education have taken part in this study. The study is a quantitative study and the research has been conducted according to a single group pretestposttest model from experimental design. For the analysis of the data, t-test, arithmetic mean, standard deviation have been used for dependent and independent groups. The findings which have been obtained in the light of the research, it has been statistically found that the STEM practices have a positive effect on the pre-service teachers' beliefs on nature of science and the constructivist approach. However, it has been found that there is no significant difference on attitudes towards scientific research. In short, it can be said that STEM practices have a positive effect on the pre-service teachers’ beliefs on nature of science and constructivist approach. Thereon, suggestions about STEM education have been made for pre-service teachers, teachers and academicians
STEM UYGULAMALARININ ÖĞRETMEN ADAYLARININ BİLİMİN DOĞASI İNANÇLARI, BİLİMSEL ARAŞTIRMA VE YAPILANDIRMACI YAKLAŞIMA YÖNELİK TUTUMLARI ÜZERİNDEKİ ETKİSİ